From the Printed Material to the Digital Age – From the Invention of Spellbook to the Cyberspace - de O. Collares, Solange Apª; Ruaro, Laurete Maria (Revista Brasileira de Aprendizagem Aberta e a Distância, 2008)
The present work is constituted by the discussion of the master’s papers in progress, those are about the spellbooks to the insertion of tecnologies in situations of the teaching-learning process in a historical-critical analysis. The initial analysis starts from the survey of the first reading textbooks used between the Empire and Republic, passing by the appearing of the press, the structural modifications of the spellbooks, until the inclusion of the digital tecnologies to the school educational proposals. It is undeniable that, on the field of spellboks and also on the reading texts more advanced, the last decades correspond to an important transition period: the nationalization of didactic literature, the noticeable improving of contents and teaching methods those incorporate since digital books until learning virtual atmospheres more complexes. In this context, the information and communication tecnologies position theirselves since the basic ways of printing until the organization of the hipertext in the cyberspace.